Long-Circulating Near-Infrared Fluorescence Core-Crosslinked Polymeric Micelles: Synthesis, Characterization, and Dual Nuclear/Optical Imaging - Yang, Zhi (2007)
We report the synthesis of PEG-coated, core-crosslinked polymeric micelles (CCPMs) derived from an amine-terminated amphiphilic block copolymer, poly(PEG-methacrylate)-b-poly(triethoxysilyl propylmethacrylate) (PPEGMA-b-PESPMA). The block copolymer self-assembled to form micellar nanoparticles, and a Cy-7-like near-infrared fluorescence dye was entrapped in the core bearing reactive ethoxysilane functional groups through a subsequent sol-gel process. The fluorescent signal of CCPMs on the molar basis was 16-fold brighter than that of Cy7. With an average diameter of 24 ± 8.9 nm, CCPMs exhibited prolonged blood half-life (t(1/2,α)= 1.25 hr; t(1/2,β)= 46.18 hr) and moderate uptake by the mononuclear phagocytic system. Significant accumulation of CCPMs in human breast tumor xenografts allowed noninvasive monitoring of the uptake kinetics with both NIRF optical and gamma imaging techniques. Our data suggest that Cy7-entrapped CCPM nanoparticles are suitable for NIRF imaging of solid tumors and have potential applications in the imaging of tumor-associated molecular markers.